The Narrative-Rhetorical Interpretation of Mark’s Theology – Application on the Motif of the Messianic Secret in Mark 9,2-10 - Brie, Ioan (2017)
This article proposes that the Gospel of Mark should be read as both a historical and a theological document. Mark is a theologian who writes theology as a story. He doesn’t simply write history, but he presents theological ideas in narrative form. Considering this fact, one must take into account the narrative-rhetorical method in the hermeneutic of Mark’s Gospel. The historical and theological character of the Gospel requires one to observe two complementary perspectives over the meaning of the book: the perspective of narration’s hero and the perspective of the reader of the Gospel. The author of this present study employs the narrative-rhetorical interpretation as method of research on Mark’s Christology, exemplifying the usage of the method in interpreting the Messianic secret motif in Jesus’ transfiguration pericope (Mark 9,2-10).
Keywords: Tradition; the perspective of the hero; the Messianic secret; reader perspective; READER; Narrative Theology; Narration; Markan theology; Mark; Interpretation; History; Hero; Christology